STUDY ON THE COMPILATION OF TYPICAL EXCITATION SPECTRUM OF SUSPENSION DYNAMIC K＆C TEST - FENG JinZhi; FU DaoQi; ZHENG SongLin; ZHENG GuangLei; XUE HaiLong; LIN Yang (Jixie qiangdu)
The traditional quasi-static K＆C characteristic test can not reflect the hysteresis effect caused by shock absorber damping and bushing viscoelasticity comprehensively and effectively, but the suspension dynamic K＆C characteristic test can make up the deficiency of the quasi-static characteristic test.Development of dynamic K＆C test involves two aspects of excitation spectrum and performance evaluation of the research content, in this paper, A class A sedan for the study of the carrier, through A skid pad road load spectrum sampling test and simulation analysis, through the bench test iterations, designed the suspension K＆C dynamic characteristic test of typical excitation spectrum, and its validity is verified by bench test and virtual test.The results show that the dynamic characteristics of the suspension can be reflected effectively by using the typical excitation spectrum designed in this paper, which provides some support for the research of wheel positioning parameters and the development of K＆C test technology.